PEMBATASAN-PEMBATASAN KONSTITUSIONAL KEKUASAAN PRESIDEN SESUDAH PERUBAHAN UUD 1945 - Soenobo Wiryosoegito (Jurnal Idea Hukum, 2015)
The slide down of President Soeharto in 1998, then turned mainly to the reform scedule of changes or amendments to the Constitution. After the change of Constitution occurring shift of power from the hands of the President of the legislation to the House of Representative. The powers of the President of the much reduced, for example: Judges no longer appointed by the President, but rather put forward by the Commission for the requested Judicial House approval, further defined by the President. Power House were enlarged in such a way, so that it can be said almost all fields of power President entered by Parliament.Keywords: limitations, the power of President and Parliamen